Outcomes associated with proton pump inhibitors and distal radius fractures: A post-hoc comparative analysis. Issue 8 (August 2022) - Klifto, Kevin M.; Ruch, David S.; Mithani, Suhail K.; Pidgeon, Tyler S.; Richard, Marc J.; Klifto, Christopher S.
Abstract: Long-term, high-dose, daily proton pump inhibitors (PPI) may impact outcomes associated with distal radius fractures (DRF). The hypothesis was that differences existed in patient demographics, but there existed no differences in injury patterns, interventions, post-operative complications, and patient-reported outcomes between patients not on a PPI and patients on a PPI with a DRF. Methods: An IRB-approved, post-hoc analysis of patients with DRF from 2012 through 2018 was performed. Patients included were age ≥18 years, sustained a DRF, had completed medical and medication records, Quick Disabilities of the Arm, Shoulder and Hand (DASH) scores, Global Assessment of Functioning (GAF) scores, visual analogue scale (VAS) pain scores, and a minimum of 1-year follow-up. Patients were stratified into two cohorts. Cohort one patients had no prescription or over-the-counter PPI use (no PPI cohort). Cohort two patients had adherence to a long-term, high-dose, daily PPI (PPI cohort). Results: Two hundred and eighty-one DRF patients were included. Of these 281 patients, 240 were in the no PPI cohort and 41 were in the PPI cohort. Patients in the PPI cohort had more median nerve injuries (12% versus 3%, p  = 0.025) and radial shaft fractures (5% versus 0%, p  = 0.020), less contralateral upper extremity injuries (0% versus 4%, p  = 0.001), and more post-operative nonunions (7% versus 1%, p  = 0.029) compared to patients in the no PPI cohort. Conclusions: Long-term, high-dose, daily PPI's may be associated with more median nerve injuries and radial shaft fractures, less contralateral upper extremity injuries, and more post-operative nonunions compared to DRF patients not on a PPI.